Is terrorism, poverty, and refugees the dark side of globalization? - Ruiz Estrada, Mario Arturo; Park, Donghyun; Khan, Alam; Tahir, Muhammad (Springer Verlag, 2019)
We present a new model on the impact of terrorism on the Deglobalization process. The channels are faster poverty expansion, largest flows of refugees, expansion of trade protectionism, and last but not least, the dramatic expansion of economic desgrowth. This new model is entitled “The Deglobalization Global Evaluation Model (DGE-Model)”. The objective of the DGE-Model is to offer policy-makers and researchers a new analytical tool to study the impact of terrorism on the Deglobalization process of Muslim countries. The applicability of the DGE-Model is not limited to a specific group of Muslim countries or regions, nor is it constrained by the development stage. In short, the DGE-Model is a simple, flexible and versatile tool to study the link between terrorism and Deglobalization. Finally, we apply the DGE-Model to three Muslim countries, namely Syria, Iraq, and Afghanistan. Our sample period is 1999–2018, a period which witnessed acceleration of Deglobalization and expansion of terrorism in those three countries. © 2019, Springer Nature B.V.